Age as a Determinant of the Effectiveness of Intravaginal Sponges Impregnated with Progestin and Equine Chorionic Gonadotropin for Multiple Births Induction of Awassi Ewes. (14th March 2023) - Daham, Abbas; Jaber, Ali; Al-Saaidi, Jabbar
Abstract : The present study was conducted to evaluate the role of age in the effectiveness of intravaginal progestin-impregnated sponges (IPIS) along with equine chorionic gonadotropin (eCG) on the multiple birth rates of Awassi ewes. One hundred mature ewes (live weight was 35–40 kg and age 2–5 years) were allocated to three groups according to their ages ( n = 29, 2-3 years; n = 34, 3-4 years; and n = 37, 4-5 years). All ewes were impregnated with IPIS, injected with 20 mg cronolone, for 14 days, and eCG (400 IU, i.m.) at sponges withdrawal. All treated ewes came to estrus (100%); the highest twining rate was recorded in ewes aged 2-3 years, while the highest triple rate were found in those aged 3-4 years. A negative correlation coefficient was recorded between the age of treated ewes and the multiple births. In conclusion, the best age of Awassi ewes for estrus synchronization programs and multiple birth outcomes using IPIS along with eCG is 2–4 years.